International higher education students’ self-esteem: A systematic review - Nguyen, Tri Dang; McGregor, Marie (Journal of International Students, 2026)
This article systematically reviews empirical studies on self-esteem among international students in higher education. Drawing on literature published between 2014 and 2024, a comprehensive search was conducted across four major databases—Scopus, ProQuest, PsycINFO, and Web of Science—guided by clearly defined inclusion criteria. Twenty relevant studies were identified and thematically analyzed, revealing three overarching themes: social interaction, psychological health, and sense of belonging. The findings highlight the reciprocal relationship between self-esteem and both social interaction and a sense of belonging, as well as self-esteem's role in shaping psychological well-being. While reinforcing the importance of self-esteem for international student adjustment, the review also identifies notable gaps in existing research and offers directions for the future.